Dragons, witches, and sorcerers in the advocacy space of national mythology [Review: Breeva Т.N., Khabibullina L.F. 'Russian Myth' in Slavic Fantasy. Moscow, Flinta, 2016] - O.E. Osovskiy (Ученые записки Казанского университета: Серия Гуманитарные науки)
The review provides a critical analysis of the new book by T.N. Breeva and L.F. Habibullina. The authors pay attention to the phenomenon of “Russian myth” in the so-called Slavic fantasy, which is a crucial part of contemporary mass literature in Russia. The main idea of this project is to demonstrate the real influence of modern mythologies on the conscience of mass readers. This is the way the mass propaganda uses to make fiction and mass media a part of its own space. The authors have traced the genetic connection of contemporary Russian fantasy with Old Slavic folklore, European medieval literature, and Western mass culture. In this context, the special emphasis has been put on J.R.R. Tolkien's traditions and the influence of today's Anglo-American fantasy. On the basis of the detailed text analysis, we have introduced different schemes of structure and form organization, plot formation, choice of characters and chronotopes, models of myths and legends modifications and transformations. The distinctive typology of different fantasy types, from heroic and legendary to comic, has been elaborated. The most vivid examples of contemporary Russian/Slavic fantasy include the books by Yu. Nikitin, K. Pleshakov, D. Yankovsky, O. Divov, A. Mironov, I. Koshkin, V. Lezhend, V. Kolychev, V. Koval'chuk, G. Romanova, V. Sverzhin, etc.